2016
DOI: 10.1155/2016/8108691
|View full text |Cite
|
Sign up to set email alerts
|

Fire-Risk Assessment in Northern Greece Using a Modified Fosberg Fire-Weather Index That Includes Forest Coverage

Abstract: The spatial distribution of the monthly mean values for various climatological parameters in Northern Greece is derived. The corresponding data come from measurements at several meteorological stations located in Central Macedonia, Eastern Macedonia, and Thrace (CM/EMT) area in the period 1975-1997. The collected data concern high temperature and low relative humidity, as well as local forest coverage, and are utilized for the calculation of a modified Fosberg Fire-Weather Index in order to estimate the fire r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
(24 reference statements)
1
4
0
1
Order By: Relevance
“…Taking into account results from Karali et al [12], a very high number of extreme days were found for several regions, mainly in the southeast of Greece, where forest fires seem to be present in an increased concentration. The ML model results for the FFWI come in accordance with results of Kambezidis et al [64], who also found wind speed to be the best-performing component regarding correlation with the FFWI.…”
Section: Discussionsupporting
confidence: 89%
“…Taking into account results from Karali et al [12], a very high number of extreme days were found for several regions, mainly in the southeast of Greece, where forest fires seem to be present in an increased concentration. The ML model results for the FFWI come in accordance with results of Kambezidis et al [64], who also found wind speed to be the best-performing component regarding correlation with the FFWI.…”
Section: Discussionsupporting
confidence: 89%
“…Some include very simple algorithms combining temperature and humidity [16,17], while others are sophisticated tools which can be used to estimate not only the probability of a fire but also its rate of spread and severity [18,19]. In general, ignition of a fire is related to both the prevailing atmospheric conditions and the local geomorphological structure, among any number of other anthropogenic factors that are not easily quantified [20].…”
Section: Introductionmentioning
confidence: 99%
“…Eastern or Western Australia, Canada, United States of America). From the above, some of them have been modified, adopted and calibrated in order to be applicable in other regions (Arpaci et al, 2013;Dimitrakopoulos et al, 2011a;Elhag and Boteva, 2017;Kambezidis and Kalliampakos, 2016;Tatli and Türkeş, 2014). This section provides information on the most worldwide used fire danger or drought indices and fire danger rating systems, in chronological order of appearance 4 .…”
Section: Wildfires In Greecementioning
confidence: 99%
“…FFWI has been applied to estimate the fire weather severity in the chaparral ecosystems of the Mediterranean-climate southern California during Santa Anna wind events (Moritz et al, 2010;Nauslar et al, 2018). In France, Barbero et al (2019) used the FFWI in a modelling framework for resolving complex relationships linking weather-to-climate variability associated with the occurrence of large wildfires, while Kambezidis and Kalliampakos (2016) introduced a modification of the FFWI that included forest coverage to assess the fire risk in Northern Greece (Central, Eastern Macedonia, Thrace). Goodrick (2002) also modified the FFWI to take into account the impact of precipitation to the index, improving its relationship with the burnt area.…”
Section: Chandler Burning Index (Cbi)mentioning
confidence: 99%